The role of Innovation Hubs taking start-ups from idea to business. The case of Nairobi, Kenya - Natalie Chirchietti (Hochschule Bonn-Rhein-Sieg, Internationales Zentrum für Nachhaltige Entwicklung (IZNE), 2017)
In recent years, there has been a growing interest in the start-up scene in sub-Saharan Africa. "Silicon Savannah" is today widely used to describe the thriving IT industry in and around Nairobi. Kenya's geographical advantage, its favorable economic reforms, and mature start-up ecosystem makes it stands out positively. Since a lot of hype exists around the start-up scene many investors are drawn to it, but in reality very few start-ups are investment-ready. The increasing start-up requirements and needs force incubators to diversify their offer. In contrast, to traditional incubators, an Innovation Hub (Hub) is characterized based on the concept of open innovation and collaboration. A Hub nurtures an enabling environment where a community of entrepreneurs can grow. At the same time, it serves as a nexus point for the local start-up community, investors, academia, technology companies and the wider private sector. It aims to create a structure where people serendipitously interact with others that they would not typically meet. Considering the great interest for and the large amounts of money invested in Hubs by governments, universities, private companies and other interested parties, not only researchers have been raising the question of the actual benefit of Hubs. This research study aims to investigate to what extent the support offered by the Hubs is tackling the challenges faced by start-ups in Nairobi, Kenya. The analysis can serve as a basis for identifying strength and weaknesses in the Hub models.
urn:nbn:de:hbz:1044-opus-33622
Keywords: M13; 330; Entrepreneurship; Innovation Hubs; Start-ups; Kenya